DEVELOPMENT OF HEALTH COMPETENCE OF CHILDREN WITH DIABETES MELLITUS IN THE SUMMER CAMP ENVIRONMENT - Čergelytė-Podgrušienė, Indrė; Gudžinskienė, Vida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Diabetes mellitus is becoming a leading disease in paediatric endocrinology, which causes health problems and complications that can shorten life expectancy. The object of the research is the development of health competence of children with diabetes mellitus in the summer camp environment. Research aim is to reveal the development of health competence of children with diabetes mellitus in the summer camp environment. Tasks: 1) to identify the development of health competence in the environment of summer camps; 2) to reveal health topics being discussed by children in summer camps; 3) to reveal pedagogical interactions between the educator and the students in the environment of summer camps. Research methods: theoretical: analysis, generalisation and systematisation of scientific literature; empirical: document analysis. The research found that not only does the environment of summer camps contribute to the development of health competence of children with diabetes mellitus but it also encourages them to fully get used to living with the disease and creates a favourable educational environment that encourages communication. The research revealed that in the summer camp environment children discuss the following topics: blood sugar control, causes of diabetes mellitus and independence in managing the disease. The summer camp environment is friendly, active as well as engaging and tolerant of learner interaction.